Unraveling The Impact: Online Customer Review, Price, and Booking Decision at We Hotel Lubuklinggau Via Traveloka - Saputra, Panji; Ferdian, Feri (Akademi Komunitas MAPINDO, 2024)
Online customer reviews and prices are a thing inseparable from the ordering decision, positive reviews fromguests and affordable prices will make prospective guests make reservations at We Hotel Lubuklinggau viaTraveloka. This study aimed to examine the effect of online customer reviews on booking decisions at We HotelLubuklinggau and the effect of price on booking decisions at We Hotel Lubuklinggau. This study employed acausal associative approach to quantitative research. Direct distribution of surveys to We Hotel Lubuklinggauguests provided data, allowing for the creation of a Likert-scale sample of 121 responses from 2,068 customerswho made reservations at online travel agencies between January and December 2023. Partial Least SquareStructural Equation Modeling (PLS-SEM) is the data analysis method used. A total of 36 percent of therespondents were between the ages of 17-25. This research found that online customer reviews are animportant factor in increasing booking decisions at We Hotel Lubuklinggau. and Price has a significant influenceon booking decisions at We Hotel Lubuklinggau. This research concludes that online customer reviews andprice determine guests' decisions in making reservations at We Hotel Lubuklinggau via Traveloka.Keywords: Booking Decision, Online Customer Review, Price